Chris Ali and the Rationality of Military Rules in Nigeria - Oyenuga, Olukayode Felix; Babatunde, Odunlami (NIU Journal of Social Sciences, 2019)
An undeniable factor in the history of Nigeria is the intervention of the military class with governance. While some scholars justify this, others sees it as an aberration that must be permanently rooted out. Scholars of Plato’s persuasion radically dismissed the rationality of military rule, but an intense study of the Africa political situation shows that military involvement in politics is compulsory particularly in a polity like Nigeria. This paper explores the problem with democracy in Nigeria and defined the role of military in line with Chris Allis short span and corrective ideology